Efektivitas Model Pembelajaran Berbasis Proyek terhadap Keterampilan Menulis Pantun Nasihat Siswa Kelas VII SMP Negeri 04 Kepahiang - Adellia, Zenda; Noermanzah, Noermanzah; Purwadi, Agus Joko (UNIB Press, 2025)
Writing pantun is still a difficult skill to master for students at SMP Negeri 04 Kepahiang, especially in writing sampiran and isi as well as difficulties in using rhyme. One of the learning models that is predicted to affect students' pantun writing skills is the project-based learning model. Therefore, the purpose of this study is to determine the effectiveness of the project-based learning model on students' pantun writing skills. The experimental method is used to implement and determine the effectiveness with a pretest-posttest design with one group. The research sample was 25 Class VII A students of SMP Negeri 04 Kepahiang who were selected by purposive sampling. The test used was a performance test for writing advice pantun. Statistical methods for analyzing data include the Shapiro-Wilk test for normality and the t-test. The study found that between the pretest and posttest, participants' scores increased from 49.12 to 77.32 on average. In the project-based learning model, students go through a series of steps including identifying problems through basic questions, creating project designs, creating work plans, implementing and monitoring projects, presenting results for testing, and reflecting and evaluating the experience. The research findings show that the project-based learning paradigm does have an influence on the capacity to write advice pantun. The results show that there is an impact of the project-based learning model on the capacity to create advice pantun. T-count is greater than t-table, which indicates that Ha is accepted and Ho is rejected.